Bibliometric analysis of social entrepreneurship in gastronomy tourism - Celebi, Duygu (Array, 2020)
The definition of "entrepreneurship" briefly stands for setting up a new business by taking financial and other risks to gain profits. Phenomenon of “social entrepreneurship” has emerged as a follow up concept of entrepreneurship, as a critical issue in the context of both improvement and wellbeing of societies. Social entrepreneurship focuses on social problems rather than profit maximization and is especially important for gastronomy tourism due to the social local benefits as cultural integration and employment it brings. In order to understand the promising research areas and explore the research gap in the gastronomical social entrepreneurship applications, bibliometric analysis is chosen since studies are limited in the gastronomy tourism as well as social entrepreneurship. The research in subject area consisted on keywords that are used as search items for articles title section to select articles that are more accurate for the aim of the research. The analysis shows that there are 20 articles with the combination of related key word variations. When the methodologies of the related articles is analyzed, it is understood that qualitative research with multiple and comparative case study is chosen for almost all the related articles. The reason might be due to the characteristics of the research topic and novelty, thus, rarity of true to life gastronomical social innovation applications. This study is expected to guide future studies by providing general overview of the studies and the research gap in social entrepreneurship and gastronomy tourism.